The Impact of Evidence-Based Parent Education in Organized Youth Sport: A Pilot Study. Issue 2 (3rd April 2017) - Dorsch, Travis E.; King, Michael Q.; Dunn, Charles R.; Osai, Keith V.; Tulane, Sarah
Abstract : Although existing literature in organized youth sport illuminates developmentally appropriate parent involvement behaviors, practitioners have yet to effectively disseminate evidence-based tools and strategies to parents. The purpose of the present pilot study was to design, implement, and assess an evidence-based education program for parents in organized youth sport. Thirty-nine fathers and 42 mothers from 7 youth soccer teams were assigned to full, partial, or nonimplementation conditions. Parents and their sport-participating children (41 boys, 40 girls) were administered surveys at pre- and postseason. Data reveal a positive impact of the implementation on aspects of parent involvement, the parent–child relationship, and salient child outcomes.